The Long‐Term Benefit of Liver Transplantation for Hepatic Metastases From Neuroendocrine Tumors. Issue 10 (9th June 2016) - Mazzaferro, V.; Sposito, C.; Coppa, J.; Miceli, R.; Bhoori, S.; Bongini, M.; Camerini, T.; Milione, M.; Regalia, E.; Spreafico, C.; Gangeri, L.; Buzzoni, R.; et al.
Abstract : Selection criteria and benefit of liver transplantation for hepatic metastases from neuroendocrine tumors (NETs) remain uncertain. Eighty‐eight consecutive patients with metastatic NETs eligible for liver transplantation according to Milan‐NET criteria were offered transplant (n = 42) versus nontransplant options (n = 46) depending on list dynamics, patient disposition, and age. Tumor burden between groups did not differ. Transplant patients were younger (40.5 vs. 55.5 years; p < 0.001). Long‐term outcomes were compared after matching between groups made on multiple Cox models adjusted for propensity score built on logistic models. Survival benefit was the difference in mean survival between transplant versus nontransplant options. No patients were lost or died without recurrence. Median follow‐up was 122 months. The transplant group showed a significant advantage over nontransplant strategies at 5 and 10 years in survival (97.2% and 88.8% vs. 50.9% and 22.4%, respectively; p < 0.001) and time‐to‐progression (13.1% and 13.1% vs. 83.5% and 89%; p < 0.001). After adjustment for propensity score, survival advantage of the transplant group was significant (hazard ratio = 7.4; 95% confidence interval (CI): 2.4–23.0; p = 0.001). Adjusted transplant‐related survival benefit was 6.82 months (95% CI: 1.10–12.54; p = 0.019) and 38.43 months (95% CI: 21.41–55.45; p < 0.001) at 5 and 10 years, respectively. Liver transplantation for metastatic NETs under restrictive criteria provides excellent long‐term outcome. Transplant‐related survival benefit increases over time and maximizes after 10 years. Abstract : This comparative study from Milan establishes restrictive criteria for patient selection in cases of liver metastases from neuroendocrine tumors and demonstrates a significant 10‐year survival benefit of liver transplantation that justifies the use of donated organs for this rare indication. See Trotter's editorial onpage 2775 .